2021
DOI: 10.1017/s0003055420001136
|View full text |Cite
|
Sign up to set email alerts
|

Why Austerity? The Mass Politics of a Contested Policy

Abstract: The effects of austerity in response to financial crises are widely contested and assumed to cause significant electoral backlash. Nonetheless, governments routinely adopt austerity when confronting economic downturns and swelling deficits. We explore this puzzle by distinguishing public acceptance of austerity as a general approach and support for specific austerity packages. Using original survey data from five European countries, we show that austerity is in fact the preferred response among most voters. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 45 publications
6
71
2
2
Order By: Relevance
“…strate the ability of the design to detect distinct patterns on some key attributes that vary cross-nationally; Bechtel and Scheve (31) report that on many climate change policy attributes, countries agree, although on sanction valuations, they disagree; Bansak and coworkers (26) find that the European public agrees on many concerns regarding asylum seekers but again, that the country samples disagree on others, such as reasons for migrating and country of origin; the AMCEs estimated by ref. 32 As our review summarized in Table 1 indicated, many of the governments of our sampled countries have prioritized COVID-19 vaccination for individuals who are at high risk of death from the virus and to a lesser extent, those at high risk of contracting and transmitting the virus. Similarly, in Fig.…”
Section: Global Covid-19 Vaccine Allocation Prioritiesmentioning
confidence: 99%
See 1 more Smart Citation
“…strate the ability of the design to detect distinct patterns on some key attributes that vary cross-nationally; Bechtel and Scheve (31) report that on many climate change policy attributes, countries agree, although on sanction valuations, they disagree; Bansak and coworkers (26) find that the European public agrees on many concerns regarding asylum seekers but again, that the country samples disagree on others, such as reasons for migrating and country of origin; the AMCEs estimated by ref. 32 As our review summarized in Table 1 indicated, many of the governments of our sampled countries have prioritized COVID-19 vaccination for individuals who are at high risk of death from the virus and to a lesser extent, those at high risk of contracting and transmitting the virus. Similarly, in Fig.…”
Section: Global Covid-19 Vaccine Allocation Prioritiesmentioning
confidence: 99%
“…It is interesting to note that other large multination conjoint survey projects also find considerable cross-national similarities, although again, these results demonstrate the ability of the design to detect distinct patterns on some key attributes that vary cross-nationally; Bechtel and Scheve ( 31 ) report that on many climate change policy attributes, countries agree, although on sanction valuations, they disagree; Bansak and coworkers ( 26 ) find that the European public agrees on many concerns regarding asylum seekers but again, that the country samples disagree on others, such as reasons for migrating and country of origin; the AMCEs estimated by ref. 32 are, for the most part, similar for Spain and Italy, although they differ on support for corporate tax increases; and ref. 27 finds distinct patterns of emigration destination preferences for Chinese and Indian emigrants vs. their British and Chilean counterparts.…”
mentioning
confidence: 93%
“…I stack the data so each observation corresponds to one profile and estimate OLS regression models predicting responses (1 = "Yes, should be possible") with indicators for each of the treatments (binning continuous treatments as illustrated in Figure 2; see Bansak et al, 2019) and a vector of pretreatment controls to improve the precision of my estimates (respondent gender, ethnoracial identity, age, ideological self-placement, party affiliation, and frequency of religious attendance). The analysis includes 5640 observations for Study 1 and 4063 for Study 2.…”
Section: Resultsmentioning
confidence: 99%
“…7 Originally, all municipalities were subject to the fiscal rule, but in 2001 those below 5,000 inhabitants were excluded. In 2013, the threshold was lowered to 1,000, 6 Possible explanations are that voters are fiscally conservative (Peltzman, 1992), that leaders implement fiscal austerity in times and as part of policy packages that allow them to electorally survive these reforms (Bansak et al, 2020), or that the divergent framing of the same issue provided by partisan media mitigates voter responses (Barnes and Hicks, 2018). 7 The main goal of fiscal rules is to achieve fiscal sustainability.…”
Section: Municipal Fiscal Rulementioning
confidence: 99%